PENGARUH KEPUASAN MITRA USAHA DAN KEPERCAYAAN MITRA USAHA TERHADAP LOYALITAS MITRA USAHA PT. ANGKASA PURA I DI BANDAR UDARA INTERNASIONAL I GUSTI NGURAH RAI BALI - Sastra Mahaesa, I Gede (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This research aimed to determine and analyze the magnitude of influence of business partners satisfaction on the loyalty of business partners, to determine and analyze the magnitude of the influence of business partners trust on the loyalty of business partner, and to found out and analyze the effect of business partners satisfaction and business partners trust together on the loyalty of business partners. This research method used a qualitative approach. Data collection techniques used a questionnaire. The population in this research were all permanent business partners of I Gusti Ngurah Rai International Airport Bali as many as 30 with 40 outlets, to avoid relatively small errors or called saturated sampling, namely 40 outlets as respondents with the position of Outlet Manager. The results of the research showed that: (1) there was a positive and significant effect of business partners satisfaction on the loyalty of business partners of PT. Angkasa Pura I at I Gusti Ngurah Rai International Airport Bali with a determination, (2) there was a positive and significant effect of business partners trust on the loyalty of business partners of PT. Angkasa Pura I at I Gusti Ngurah Rai International Airport Bali with a determination, (3) there was a positive and significant effect of business partners satisfaction and business partners trust together on the loyalty of business partners of PT. Angkasa Pura I at I Gusti Ngurah Rai International Airport Bali with a determination of 86.5% and the remaining 13.5% was influenced by other factors not examined